2021
DOI: 10.3389/ffgc.2020.620436
|View full text |Cite
|
Sign up to set email alerts
|

Partial Retention of Legacy Trees Protect Mycorrhizal Inoculum Potential, Biodiversity, and Soil Resources While Promoting Natural Regeneration of Interior Douglas-Fir

Abstract: Clearcutting reduces proximity to seed sources and mycorrhizal inoculum potential for regenerating seedlings. Partial retention of legacy trees and protection of refuge plants, as well as preservation of the forest floor, can maintain mycorrhizal networks that colonize germinants and improve nutrient supply. However, little is known of overstory retention levels that best protect mycorrhizal inoculum while also providing sufficient light and soil resources for seedling establishment. To quantify the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 131 publications
0
8
0
Order By: Relevance
“…Tree diversity and population dynamics are known to be affected by the resident mycorrhizal fungal community’s composition (Tedersoo et al 2020), while the direct mechanisms and the mycorrhizal community characteristics and their effects on forest structure are less understood, although important. Recently, (Simard et al 2021)showed that clearcutting decreased the cover of EM-hosts, while promoting AM-hosts in the post-harvest year. In this study, we examined the diversity of a mycorrhizal community in a forest plot containing a mixture of EMF- and AMF-host trees that live in close proximity and share many available resources (Rog et al 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Tree diversity and population dynamics are known to be affected by the resident mycorrhizal fungal community’s composition (Tedersoo et al 2020), while the direct mechanisms and the mycorrhizal community characteristics and their effects on forest structure are less understood, although important. Recently, (Simard et al 2021)showed that clearcutting decreased the cover of EM-hosts, while promoting AM-hosts in the post-harvest year. In this study, we examined the diversity of a mycorrhizal community in a forest plot containing a mixture of EMF- and AMF-host trees that live in close proximity and share many available resources (Rog et al 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Paired with the influence of fire, is the importance of established trees as sources of inoculum for regenerating seedlings (Haskins and Gehring, 2005;Hubert and Gehring, 2008;Teste et al, 2009;Mueller et al, 2019;Simard et al, 2021). Established trees can provide inoculum directly [from their root system at immediate spatial scales (∼5 m)] (Teste et al, 2009) or indirectly [nearby stands that host ECMF that disperse to regenerating seedlings at local scales (∼1 km)] (Trusty and Cripps, 2011;Policelli et al, 2019).…”
Section: Assessment Of Ectomycorrhizal Fungi At a Whitebark Pine Plan...mentioning
confidence: 99%
“…Nevertheless, tropical forests suffer from human disturbance which tends to degrade and destroy them ( Morris, 2010 ). In tropical forests, particularly in developing economies, human interactions with forest ecosystems result in forest destruction and loss, and remain as an important agent of change in forest structure ( FAO and UNEP, 2020 ) and functioning ( Simard et al., 2021 ). Although there are many human activities responsible for this phenomenon, logging and agricultural land use are the major drivers of degradation and deforestation, respectively ( Acheampong et al., 2019 ; Morris, 2010 ; Nias, 2013 ; Rajpar, 2018 ; Shvidenko, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Selective logging is often targeted at removing selected trees which creates canopy gaps ( Seidler and Bawa, 2001 ). Conversely, clear-cut logging removes either all or almost all trees in the forest ( Simard et al., 2021 ), indicating higher disturbance intensity of this logging regime. Logging related activities such as creation of logging roads and skid trails also contribute to cause further forest destruction ( Magrach et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation